Implementation of PjBL-STEM Based with Online Game to Improve Critical Thinking Ability - Dewi, Yessica Chrisna; Yusup, Muhamad; Fathurohman, Apit; Rahman, Nor Farahwahidah Abdul (FKIP Universitas Lampung, 2024)
This study investigates the effectiveness of project-based learning integrated with STEM (PjBL-STEM) using online games to enhance critical thinking skills among junior high school students on the topic of energy and its changes. A mixed-method approach with a sequential explanatory design was used in this study. The quantitative phase involved pretests and posttests using a standardized critical thinking skills test, while the qualitative phase included observations of student activities during learning. This study was conducted at SMP Negeri 03 Belitang Madang Raya, involving eighth-grade students divided into experimental and control groups in the odd semester of the 2024-2025 academic year. The experimental group (32 students) implemented the PjBL-STEM model using Minecraft Education, while the control group (23 students) received conventional instruction. Data analysis included Rasch modeling for pretest and posttest results, N-gain calculations to measure learning effectiveness, and thematic analysis of observation data to assess student engagement and application of STEM concepts. The findings revealed a significant improvement in the experimental group's critical thinking skills, with an N-gain score of 0.60 (effective category) compared to 0.04 (less effective category) in the control group. Projects such as wind, hydroelectric, and solar power plants, developed in Minecraft Education, highlighted students' ability to integrate scientific knowledge, engineering principles, and teamwork. Observations showed active engagement and collaboration among experimental group students during the project design and implementation phases, which were absent in the control group. This study demonstrates that integrating online games into PjBL-STEM provides an effective approach to enhancing 21st-century skills. The results underscore the potential for adapting this model to diverse educational settings and materials. However, differences in students' technological skills remain challenging, suggesting additional support and scaffolding. Keywords: critical thinking skills, energy, minecraft education, online games, PjBL-STEM DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1361-1377